2013
DOI: 10.1021/nn400322f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, andIn VivoEfficacy of Shell Cross-Linked Nanoparticle Formulations Carrying Silver Antimicrobials as Aerosolized Therapeutics

Abstract: The use of nebulizable, nanoparticle-based antimicrobial delivery systems can improve efficacy and reduce toxicity for treatment of multi-drug-resistant bacteria in the chronically infected lungs of cystic fibrosis patients. Nanoparticle vehicles are particularly useful for applying broad-spectrum silver-based antimicrobials, for instance, to improve the residence time of small-molecule silver carbene complexes (SCCs) within the lung. Therefore, we have synthesized multifunctional, shell cross-linked knedel-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 60 publications
3
60
0
Order By: Relevance
“…Shah and co-workers have published in vivo data showing SCKs loaded with Ag + and or SCC1 required lower amounts of Ag + (up to 16-fold less) and a lower number of administered doses to achieve the same therapeutic outcome as SCC1 only. [12] In another study, SCC10, a derivative of SCC1, encapsulated into l -tyrosine polyphosphate (LTP) nanoparticles also exhibited improved drug dosing, sustained release and better mice survival outcomes when compared with the non-capsulated SCC10. [11] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Shah and co-workers have published in vivo data showing SCKs loaded with Ag + and or SCC1 required lower amounts of Ag + (up to 16-fold less) and a lower number of administered doses to achieve the same therapeutic outcome as SCC1 only. [12] In another study, SCC10, a derivative of SCC1, encapsulated into l -tyrosine polyphosphate (LTP) nanoparticles also exhibited improved drug dosing, sustained release and better mice survival outcomes when compared with the non-capsulated SCC10. [11] …”
Section: Resultsmentioning
confidence: 99%
“…[10] To investigate the sustained release of silver, silver incorporated into larger molecules is currently under consideration for in vivo applications. [11, 12] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antimicrobial-and antiviral-properties of nanosilver including toward antibioticresistant strains has been studied extensively. [28][29][30][31] The antibacterial activity of nanosilver toward Escherichia coli is expressed by surface area, rather than mass or number concentrations. [32,33] Several previous reports showed that the interaction between Ag ions and the constituents of the bacterial membrane caused structural changes, damage to the membranes and the intracellular metabolic activity, and therefore cell death.…”
Section: Introductionmentioning
confidence: 99%